A poly(pyridine–pyrrole) foldamer that binds isolated water molecules. Issue 26 (13th June 2019) - Meng, Fanxuan; Zhang, Xiaoshuai; Sarma, Tridib; Yuan, Ningning; Yin, Ying; Duan, Zhiming; Lei, Chuanhu; Qian, Qun; Ding, Lili; Zhang, Zhan
Abstract : A poly(pyridine–pyrrole) foldamer binding isolated water molecules were designed, synthesized and characterized. Abstract : Poly(pyridine–pyrrole) foldamers were designed, synthesized and characterized. X-ray diffraction analyses revealed that two water molecules were encapsulated by the foldamer possessing quasi-hydrophilic terminal groups. Both the oxygen–oxygen distance and the O–H⋯O angle indicated that there was no effective hydrogen bonding between the two trapped water molecules.